2017
DOI: 10.1080/24750573.2017.1368365
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural sleep problems in previously untreated children with attention deficit hyperactivity disorder

Abstract: OBJECTIVE: Although sleep symptoms are not included in the diagnostic criteria of attention deficit hyperactivity disorder (ADHD), these problems are common in children with ADHD. The presence of sleep problems was associated with impairment in functionality and increase in ADHD intensity. The aims of the study were to evaluate sleep problems of children with ADHD who had never received any psychiatric treatment and investigate the effects of these problems in functionality. METHODS: The present study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
2
11
0
2
Order By: Relevance
“…It is known that children with ADHD or ASD are at increased risk of sleep problems. [28][29][30] Our findings confirm that both fatigue and sleep problems are over-represented in children with a diagnosis of ADHD or ASD. Treatment with CNS stimulants may have an effect on sleep in children with ADHD, but the individual variation in drug response and sleep problems is not completely understood.…”
Section: Discussionsupporting
confidence: 73%
“…It is known that children with ADHD or ASD are at increased risk of sleep problems. [28][29][30] Our findings confirm that both fatigue and sleep problems are over-represented in children with a diagnosis of ADHD or ASD. Treatment with CNS stimulants may have an effect on sleep in children with ADHD, but the individual variation in drug response and sleep problems is not completely understood.…”
Section: Discussionsupporting
confidence: 73%
“…For persistent sleep problems, risk factors were found to be internalizing and externalizing symptoms severity, medication use and ADHD symptoms severity, whereas for transient sleep problems, poor parental mental health and co-occurring internalizing and externalizing behaviors were found to be risk factors (Lycett, Sciberras, et al, 2014). Using the CSHQ, it was also found that elevated scores on individual subscales (sleep onset latency, night waking, daytime sleepiness, sleep duration, parasomnias, daytime sleepiness) among the ADHD cohort were positively associated with a variety of parent reported externalizing behavioral problems (social, attentional and disruptive behaviors) and functional impairment (family, school, life skills, social activities and risky actions) (Aronen et al, 2014; Choi et al, 2010; Eyuboglu & Eyuboglu, 2018). Additionally, subjective reports by parents revealed that sleep problems emerging early for children (aged 6–8 years) with ADHD ( n = 177) are uniquely associated with co-occurring internalizing and externalizing behaviors (Sciberras et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…DEHB, çocuk ve ergenlerde en sık görülen psikiyatrik bozukluklardan birisi olup bir meta-analiz çalışmasında tüm dünyada sıklığının %5,29 olduğu bildirilmiştir [3] [2]. Ülkemizde 83 DEHB tanılı ve tedavi almamış çocuk ve ergenle yapılmış bir çalışmada, sağlıklı kontrollere göre DEHB tanısı alan grubun anlamlı düzeyde uyku sorunu yaşadıkları ve bunun işlevselliği etkilediği saptanmıştır [15]. Owens ve arkadaşları, 46 DEHB tanılı ve tedavi almamış okul çağı çocuğu ile yaptıkları bir çalışmada, sağlıklı kontrollere göre hem kendilerinin, hem de ebeveynlerinin uyku sorununu anlamlı düzeyde bildirdiklerini saptamışlardır [16].…”
Section: Discussionunclassified
“…Bu, ergenlerin uyku ihtiyacını daha az hissetmeleri ile ilgili olabilir ve sorun olarak algılamamış olabilirler. Eyüboğlu ve Eyüboğlu'nun araştırmalarında [15] elde ettikleri sonuçlardan farklı olarak, öğretmenin bildirdiği işlevsellik değerlendirmesinde benlik saygısında uyku sorunu ile ilişki saptanması dışında diğer alanlardaki işlevsellik etkilenmesi ile uyku arasında bir ilişki saptanmamıştır. Bugüne kadar çocuk ve ergenlerde yeme tutumları ve DEHB arasındaki ilişkinin sınırlı sayıda çalışma ile araştırıldığı dikkat çekmektedir [17].…”
Section: Discussionunclassified